The Role of Digitalization in Processes Recruitment Selection for Internship Students of PT. Pertamina Hulu Rokan - Irma Joyce Logahan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Digitalization has greatly influenced the business world, particularly in the recruitment and selection processes. With the integration of communication and information technology, recruitment has shifted from manual methods to technology-driven systems. This shift is also being experienced by companies in Indonesia, including in State-Owned Enterprises (SOEs). In this context, the purpose of this research is to examine the role of digitalization in the recruitment and selection process at PT. Pertamina Hulu Rokan (PHR). This study employs qualitative methods, using three data collection techniques: structured interviews, observations, and literature reviews. The interview samples consist of nine individuals, including students participating in PT. PHR's internship program, internship coordinator from Caltex Riau University, and Human Capital Manager at PT. PHR. The findings indicate that digitalization plays a significant role in the recruitment and selection process at PT. PHR. Key benefits include enhanced efficiency and effectiveness in time management for both recruiters and applicants, cost reduction, increased company engagement and outreach, as well as improved company branding